Perbandingan Pemahaman Konsep Fisika Dasar Berdasarkan Jalur Masuk Mahasiswa Departemen Pendidikan Fisika - Prasetyani, Eka Putri; Siti Aminah Zahrotun Nisa'; Bayu Setiaji (Indonesian Journal Publisher, 2023)
Students' understanding of Basic Physics concepts regarding Kinematics has different levels of understanding according to the entry route. This research aims to determine the comparison of understanding of Basic Physics concepts regarding Kinematics based on student entry points at the Department of Physics Education. The type of research used is experimental research. The sample used was 34 undergraduate students majoring in Physics Education who were chosen randomly. The research instrument used was a questionnaire with four multiple choice questions. Data collection techniques use Google Forms which are shared in class groups. The data obtained were analyzed using CRI (Certainty of Response Index) and Analysis of Variance (ANOVA). The research results show that there are differences in understanding of Basic Physics concepts based on entry route